Diversification and stabilization in a resource-exporting country - Egbert Gerken (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1983)
The costs and benefits of export diversification in an old non-oil commodity exporting country are the subject matter of the following analysis. In chapter 2 the causal nexus from commodity price fluctuations to domestic disturbances is developed from well-established macro- and microeconomic theory-. As both structural change and multiple distortions are central to the argument, the analysis is promising only in a quantitative multisectoral general equilibrium framework applied to some appropriate country. The case of copper-exporting Chile will be studied here. The country model is described in chapter 3 and documented in the appendix. The model experiments used for determining the costs and benefits are also designed in chapter 3. The results are presented and discussed in chapter 4 and conclusions are drawn in chapter 5.
Keywords: 330